Positive effects of dialyzable leukocyte extract (DLE) on recovery of mouse haemopoiesis suppressed by ionizing radiation and on proliferation of haemopoietic progenitor cells in vitro - Vacek, A; Hofer, M; Barnet, K; Cech, K; Pekárek, J; Schneiderová, H (International journal of immunopharmacology, 2000)
Dialyzed leukocyte extract (DLE) (Immodin SEVAC, Czech Republic) was shown to enhance the recovery of the pools of hemopoietic stem cells (CFUs) and of granulocyte-macrophage hemopoietic progenitor cells (GM-CFC) in the bone marrow in vivo, as well as to increase the numbers of leukocytes and thrombocytes in the peripheral blood of mice exposed to a sublethal dose of gamma-rays, with an ensuing increase in the numbers of mice surviving the lethal radiation dose. In experiments performed in vitro, DLE or sera of mice administered with DLE were added to cultures of intact mouse bone marrow cells containing suboptimal concentrations of hemopoietic stimulatory cytokines, namely recombinant mouse interleukin-3 (rmIL-3) or recombinant mouse granulocyte-macrophage colony-stimulating factor (rmGM-CSF); under these experimental conditions, both DLE and sera of mice administered DLE were found to increase the counts of GM-CFC colonies in the cultures. It can be hypothesized on the basis of the findings obtained in vitro that the described co-stimulating activity (CoSA) of DLE may play a role also under in vivo conditions; the enhancement of the recovery of hemopoiesis suppressed by ionizing radiation may be due to a co-operation of the stimulatory effects of DLE with the action of cytokines endogenously produced in irradiated tissues.
Keywords: Cell Division; Leukocytes; Hematopoiesis; Female; faktory stimulující kolonie; hematopoetické kmenové buňky; zvířata; myši; myši inbrední C57BL; Mice; hematopoéza; Mice, Inbred CBA; ženské pohlaví; Mice, Inbred C57BL; Hematopoietic Stem Cells; Colony-Stimulating Factors; Animals; myši inbrední CBA; leukocyty; buněčné dělení